Results 1 to 7 of 7

Thread: These are example questions from an aptitude test I found.?

  1. #1
    Join Date
    Aug 2007
    Posts
    1

    Default These are example questions from an aptitude test I found.?

    1. a=b+3(4-c) If b equals 5 and c equals 2, what is the value of a?

    2. y=3(x+5)(x-2) Which of the following formulas is equivalent to this one?

    a. y=3x2+9x-30
    b y=x2=3x-10
    c. y=3x2+3x-10
    d. y=3x2+3x-30

    3. y=x+5 Which of the following choices represents the same relationship as demonstrated in this equation?

    a y/5 x/10
    10 15
    15 20
    20 25

    b. Y is equivalent to the sum of a constant c and x, where c equals 5

    c y=(x+20)/4

    d. [table]

    Please show steps to solving these problems.

    Thanks In Advance

  2. #2
    Join Date
    Aug 2007
    Posts
    1

    Default

    1. when you substitute you get a= 5+3(4-2)
    a= 5+3*2
    a=11

    2. a. First you must do the multiplication

    y= 3(x^2-2x+5x-10)
    y=3(x^2+3x-10)
    y=3x^2+9x-30

    3. b
    I`m not really sure what you meant in a, but if I´m correct you meant that y=5 and x=10. Then, the only correct is 10/15
    I couldn´t see the table either.
    As for c, once you resolve it you get y=(x/4)+5. So, it`s not the same.

  3. #3
    Join Date
    Jun 2007
    Posts
    2

    Default

    Do your own homework!
    Powered by Yahoo! Answers

  4. #4
    Join Date
    Aug 2007
    Posts
    2

    Default

    a) - Just substitute the numbers, so the problem becomes:-

    5+ 3(4-2) - (Do the sum in brackets first then multiply the answer by 3 then add the 5)

    b) - Y=3(x-5)(x-2) - Lose the brackets first by multiplyiny what's inside by eachother - (x-5)(x-2) - First multiply the xs, then the x in the first bracket by the 2 in the 2nd, then the minus 5 in the first bracket by the x in the 2nd, then the minus 5 in the 1st by the minus 2 in the 2nd. Add together the 4 terms and multiply by the 3 outside the brackets, and you should get to one of the options given.


    3) - Should be fairly obvious from the options given - Y = x+5 so Y is 5 greater than X

    Hope this helps

  5. #5
    Join Date
    Aug 2007
    Posts
    2

    Default

    a) - Just substitute the numbers, so the problem becomes:-

    5+ 3(4-2) - (Do the sum in brackets first then multiply the answer by 3 then add the 5)

    b) - Y=3(x-5)(x-2) - Lose the brackets first by multiplyiny what's inside by eachother - (x-5)(x-2) - First multiply the xs, then the x in the first bracket by the 2 in the 2nd, then the minus 5 in the first bracket by the x in the 2nd, then the minus 5 in the 1st by the minus 2 in the 2nd. Add together the 4 terms and multiply by the 3 outside the brackets, and you should get to one of the options given.


    3) - Should be fairly obvious from the options given - Y = x+5 so Y is 5 greater than X

    Hope this helps

  6. #6
    Join Date
    Aug 2007
    Posts
    1

    Default

    1. a=b+3(4-c) If b equals 5 and c equals 2, what is the value of a?

    a = 5 + 3(4-2) - substitute for b and c

    2. y=3(x+5)(x-2) Which of the following formulas is equivalent to this one?

    a. y=3x2+9x-30
    b y=x2=3x-10
    c. y=3x2+3x-10
    d. y=3x2+3x-30

    substitute x = 1 and see were u get the same answer for y
    y=3(5+1)(1-2)

    and do the same in a b c and d, put 1 in place of x

    3. y=x+5 Which of the following choices represents the same relationship as demonstrated in this equation?

    not sure

  7. #7
    Join Date
    Sep 2007
    Posts
    6

    Default

    thank you. it helped me alot

Tags for this Thread

Bookmarks

Posting Permissions

  • You may not post new threads
  • You may not post replies
  • You may not post attachments
  • You may not edit your posts
  •